Rzeźbione światłem miast dłutem. Krakowskie retabulum ołtarza Zaśnięcia Najświętszej Marii Panny w obiektywie Stanisława Kolowcy - Kobylińska, Weronika (Artium Quaestiones, 2022)
On two occasions (around 1932–1933 and after the war, between 1946 and 1950), Stanisław Kolowca (1904–1968) undertook the task of creating the photographic documentation of the reredos of the altar of the Dormition of the Blessed Virgin Mary in Kraków (Poland). The stature of Wit Stwosz’s work – widely recognized as one of the key late Gothic masterpieces in Europe – could be the only factor legitimizing the status of Kolowca’s photographs. Nevertheless, the photographs seem to deserve a thorough analysis for other reasons as well. It should be underlined that in his project Kolowca did not focus only on the most obvious shots illustrating the altarpiece. In addition to long shots and full shots showing the characteristic iconographic motifs and portrait-type close-ups, reflecting the mastery of key figures (such as Virgin Mary or John the Baptist), the photographer also created completely unexpected compositions that go beyond the codified frames of documentary photography. Consequently, his works fundamentally problematize the concept of photographic reproduction of an art piece.